Quasi Experimental Study to Ascertain Link of PPI to Bone Profile in Healthy Individuals: Link of PPI to Bone Profile - Memon, Yasra; Shaikh, Imran Ali; Karim, Imran (Pakistan Journal of Health Sciences, 2023)
Proton pump inhibitor (PPI) is only acid blocking agent used for treating the disease known as gastroesophageal reflux (non-erosive), erosive esophagitis disease, dyspepsia disease and the peptic ulcer disease because of its efficacy and potency. However, overuse of it is examined an immediate result of absence of determination of need for steady treatment in many outdoor subjects Objective: To evaluate impact of proton pump inhibitor (PPI) on bone biochemistry in young individuals of Hyderabad. Methods: The study contained 227 young individuals of age 20-45 years, it was conducted in Liaquat University Hospital, Hyderabad City and Medicine OPD’s of Jamshoro. The research study is undertaken using Quasi experimental study. The study duration is 6 months starting from 15th March 2020 to 15th September 2020 and sampling technique is non – probability convenience. SPSS 21 software is used to analyze the data. The post stratification chi – square test is performed at the interval of 95% confidence, besides it the P-value is observed ≤ 0.05. Results: There is no effect on serum calcium and vitamin D levels with use of proton pump inhibitor PPI. P-value was observed 0.7 for the serum calcium and the p- value for Serum Vitamin D was 0.1. Conclusions: Hence, the study showed that proton pump inhibitor PPI use for less than 6 months have no effect on bone biochemistry.